Effect of Sputtering Power on the Electrochemical Properties of Low Loaded Pt Catalysts for PEM Fuel Cell - Ozdemir, Oguz Kaan (ELECTROCHEMICAL SOC JAPAN, 2015)
A series of thin Pt films were deposited by dc magnetron sputtering with different power directly on a commercial hydrophobic carbon paper substrate at room temperature. Their electrochemical properties toward the oxygen reduction reaction were investigated in 0.5 M H2SO4 solution by means of cyclic voltametry (CV) and linear sweep voltametry (LSV) on rotating disc electrode (RDE). It was found that the increase of power leads to rise in the electrochemical active surface area (EASA) slightly up to 25 W, but further increase in power decreases surface area significantly. Electrochemical surface area is reaching a maximum of 29.68 m(2) g(pt)(-1) for 25 W. Rotating disk electrode experiments, also, show that increase of power yield more active catalyst toward to oxygen reduction reaction. As a result, 25 W coating power is the optimum for the preparation of the smallest and the most active Pt particle in catalytic film. (C) The Electrochemical Society of Japan, All rights reserved.
Keywords: Coating Parameters; Electrocatalysis; ORR; Sputtered Pt Filmsi; OXYGEN REDUCTION; PT-RU; PERFORMANCE; ELECTRODES; PLATINUM; DEPOSITION; THIN; DEPENDENCE; KINETICS; LAYERS; Electrochemistry